Approaches to optimising access to NICE-approved biologic anti-TNFs for patients with rheumatoid arthritis with moderately active disease - Taylor, PC; Askari, A; Choy, E; Ehrenstein, MR; Else, S; Nisar, MK (BioMed Central, 2023)
Background Rheumatoid arthritis (RA) is a chronic inflammatory disease that is associated with joint pain and stiffness. Biologics represent some of the most effective treatments for RA, but previous guidance from the National Institute for Health and Care Excellence (NICE) has limited their use to patients with severely active disease. This has meant patients with moderately active RA have been treated as if they have an acceptable disease state, despite many cases where the inflammation has a major impact on joint damage, mobility, pain and quality of life. However, recent guideline changes (NICE TA715) have approved the use of three biologics — adalimumab, etanercept and infliximab — for the treatment of moderately active RA.